The subject matters for the professional vision of classroom management: an exploratory study with biology and mathematics expert teachers - Stahnke, Rebekka; Friesen, Marita (Frontiers in Education, 2023)
Teacher professional vision of classroom management is one crucial aspect of teacher expertise that has so far been studied without considering the role of teachers’ subjects. However, subject teaching is characterized by typical settings and activities that might require different classroom management strategies. This small-scale explorative study investigates whether twenty expert teachers from two secondary school subjects (biology and mathematics) differ in their professional vision of classroom management. Using video clips of two settings as stimuli, teachers’ eye-tracking data and retrospective think-aloud data were recorded. Think-aloud data were investigated with quantitative content analysis and epistemic network analysis. Expert teachers’ visual attention, their noticing of classroom management events, and their knowledge-based reasoning were compared for both groups. Results reveal subject-specific aspects of expert teachers’ professional vision of classroom management in terms of events noticed and their reasoning about these events. Expert biology teachers were more concerned with suggesting alternative classroom management strategies, particularly strategies addressing aspects to consider when planning activities such as providing structure or preparing the classroom. In contrast, mathematics teachers were more evaluative in their analysis of events and focused more on behavioral management or ensuring students’ engagement in the moment.